2012
DOI: 10.1002/nme.3288
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of flapping wings using a panel method and a high‐order Navier–Stokes solver

Abstract: SUMMARYThe design of efficient flapping wings for human engineered micro aerial vehicles (MAVs) has long been an elusive goal, in part due to the large size of the design space. One strategy for overcoming this difficulty is to use a multi-fidelity simulation strategy appropriately balances computation time and accuracy. We compare two models with different geometric and physical fidelity. The low-fidelity model is an inviscid doublet lattice method with infinitely thin lifting surfaces. The high-fidelity mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…As discussed in section II, the solver is similar to that used by other authors. [10][11][12][13] It should be noted that, besides their obvious limitations (inviscid, hence there is no skin friction and no separation), unsteady potential solvers have shown good agreement with experiments 13,14 and viscous simulations 12,15 for flapping wings at moderate Reynolds numbers (Re ≈ 10 3 − 10 4 ), reduced frequencies in the range 0.4 -3 and large flapping amplitudes (vertical displacement of the order of the chord of the wing). Additionally, the low computational cost of this solvers makes them excellent candidates for parametric sweeps, 16 or for optimization procedures.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…As discussed in section II, the solver is similar to that used by other authors. [10][11][12][13] It should be noted that, besides their obvious limitations (inviscid, hence there is no skin friction and no separation), unsteady potential solvers have shown good agreement with experiments 13,14 and viscous simulations 12,15 for flapping wings at moderate Reynolds numbers (Re ≈ 10 3 − 10 4 ), reduced frequencies in the range 0.4 -3 and large flapping amplitudes (vertical displacement of the order of the chord of the wing). Additionally, the low computational cost of this solvers makes them excellent candidates for parametric sweeps, 16 or for optimization procedures.…”
Section: Introductionmentioning
confidence: 78%
“…To evaluate the relation between the increment in thrust and the increment in required power, figure 6 shows the propulsive efficiency, defined in eq. (12). First of all, the propulsive efficiencies reported in figure 6 are relatively low, around 50% for all cases considered here.…”
Section: Iiic Propulsive Efficiencymentioning
confidence: 85%
See 1 more Smart Citation
“…They found that providing the wing morphing more flexibility (greater degrees of spatial and temporal freedom) improves the flapping wing design. In a recent paper, Persson et al (2012) conducted a detailed comparison between UVLM and higher-fidelity CFD methods for flapping flight. Their results indicated that the UVLM schemes produce accurate results for attached flow cases and even remain trend-relevant in the presence of flow separation.…”
Section: Introductionmentioning
confidence: 99%
“…33 In three-dimensions, the analysis becomes a little more involved due to the increased number of degrees of freedom.…”
Section: Iiib Three-dimensional Geometry Definition and Computationalmentioning
confidence: 99%